Biomechanical evaluation of a novel anterior transpedicular screw-plate system for anterior cervical corpectomy and fusion (ACCF): a finite element analysis - Huang, Shengbin; Ling, Qinjie; Lin, Xinxin; Qin, Hao; Luo, Xiang; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2023)
Background and Objective: Cervical fusion with vertebral body screw (VBS)-plate systems frequently results in limited biomechanical stability. To address this issue, anterior transpedicular screw (ATPS) fixation has been developed and applied preliminarily to multilevel spinal fusion, osteoporosis, and three-column injury of the cervical spine. This study aimed to compare the biomechanical differences between unilateral ATPS (UATPS), bilateral ATPS (BATPS), and VBS fixation using finite element analysis.A C6 corpectomy model was performed and a titanium mesh cage (TMC) and bone were implanted, followed by implantation of a novel ATPS-plate system into C5 and C7 to simulate internal fixation with UATPS, BATPS, and VBS. Internal fixation with UATPS comprises ipsilateral transpedicular screw-contralateral vertebral body screw (ITPS-CVBS) and cross transpedicular screw-vertebral body screw (CTPS-VBS) fixations.Mobility, the maximal von Mises stress on TMC, the stress distribution and maximal von Mises stress on the screws, and the maximum displacement of the screw were compared between the four groups.Compared with the original model, each group had a reduced range of motion (ROM) under six loads. After ACCF, the stress was predominantly concentrated at two-thirds of the length from the tail of the screw, and it was higher on ATPS than on VBS. The stress of the ATPS from the cranial part was higher than that of the caudal part. The similar effect happened on VBS.The screw stress cloud maps did not show any red areas reflective of a concentration of the stress on VBS. Compared with VBS, ATPS can bear a greater stress from cervical spine movements, thus reducing the stress on TMC. The maximal von Mises stress was the lowest with bilateral transpedicular TMC and increased with cross ATPS and with ipsilateral ATPS. ITPS-CVBS, CTPS-VBS, and BATPS exhibited a reduction of 2.3-22.1%, 11.9-2.7%, and 37.9-64.1% in the maximum displacement of screws, respectively, compared with that of VBS.In FEA, the comprehensive stability ranked highest for BATPS, followed by CTPS-VBS and ITPS-CVBS, with VBS demonstrating the lowest stability. Notably, utilizing ATPS for fixation has the potential to reduce the occurrence of internal fixation device loosening after ACCF when compared to VBS.